PENGARUH TEKANAN WAKTU, RISIKO AUDIT, MATERIALITAS, PROSEDUR REVIEW DAN KONTROL KUALITAS, KOMITMEN PROFESIONAL, DAN LOCUS OF CONTROL TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Survey pada Auditor di KAP Wilayah Pekanbaru, Medan, Batam, dan Padang) - Nurhardianty Kurnia Sari; Kamaliah '; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The objective of this study is to determine the effect of time pressure, audit risk, materiality, review procedures and quality control, professional commitment, locus of control on premature sign-off audit proceduress at the public accountant firm (KAP) in Pekanbaru, Batam, Medan, and Padang. This study uses primary data. Sample selection technique used is purposive sampling. The analytical method used is multiple linear regression with SPSS. Based on the overall hypothesis testing showed that time pressure, audit risk, materiality, review procedures and quality control, professional commitment, locus of control have a significant impact premature sign-off audit proceduress.Keywords: Time pressure, Audit risk, Premature sign-off audit proceduress.